The Effectiveness of Super Chinese Application for Training Mandarin Speaking Skills for Class XI IBB Students of SMA Laboratorium UM - Umaroh, Tutut Kholifah; Kurniawan, Deddy; Ventivani, Aiga (Confucius Institute Universitas Sebelas Maret, 2025)
One of the language skills used for communication purposes is speaking skills. In Mandarin, speaking skills are skills to express ideas or ideas that involve pronunciation and require proper intonation. As technology advances, learning Mandarin using applications is very helpful because of the ease of access and increasing enthusiasm for learning. For example, the Super Chinese application utilizes AI technology in materials and practice questions. Applications that utilize artificial intelligence (AI) technology are expected to support the learning process, especially learning Mandarin. This study was conducted with the aim of describing the level of students' speaking skills and determining the effectiveness of AI-based applications, one of which is the Super Chinese application. This study uses a quantitative correlational method with a pre-experimental design in the form of a one-group pretest-posttest design. The instrument used is a test instrument in the form of pretest and posttest questions. The data source used was class XI IBB SMA Laboratorium UM, totaling 24 students. Data were obtained from the average results of students' pretest and posttest scores. The data analysis techniques used were paired sample t-test, n-gain test, and pearson correlation test.The results of this study indicate that the Super Chinese application is effective in training the Mandarin speaking skills of class XI IBB students at SMA Laboratorium UM.